2019
DOI: 10.1017/jfm.2019.559
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale motions in a plane wall jet

Abstract: The plane wall jet (PWJ) is a wall-bounded flow in which a wall shear layer develops in the presence of extremely energetic flow structures of the outer free-shear layer. The structure of a PWJ, developing in still air, was studied with the focus on the large scales in the flow. Wall-normal hot-wire anemometry (HWA) measurements along with double-frame particle image velocimetry (PIV) measurements (wall-normal–streamwise plane) were carried out at streamwise distances up to $162b$, where $b$ is the slot width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 78 publications
(283 reference statements)
3
20
0
Order By: Relevance
“…Because of this disparity, in both the supercritical and subcritical currents, there exists an intermediate region above or below the velocity maximum where Reynolds shear stress ( ) and mean velocity gradient ( ) are of opposite sign resulting in negative shear production. In the supercritical current, near the inlet ( x ⪅ 60) streamwise momentum dominates stratification and negative shear production is below the velocity maximum (striped blue region) and this scenario is similar to that observed in TWJs 30 , 31 . As stratification starts to dominate ( x ⪆ 60) the influence of the near-bed layer on the interface layer dominates, and the region of negative shear production switches to above the velocity maximum (striped red region).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Because of this disparity, in both the supercritical and subcritical currents, there exists an intermediate region above or below the velocity maximum where Reynolds shear stress ( ) and mean velocity gradient ( ) are of opposite sign resulting in negative shear production. In the supercritical current, near the inlet ( x ⪅ 60) streamwise momentum dominates stratification and negative shear production is below the velocity maximum (striped blue region) and this scenario is similar to that observed in TWJs 30 , 31 . As stratification starts to dominate ( x ⪆ 60) the influence of the near-bed layer on the interface layer dominates, and the region of negative shear production switches to above the velocity maximum (striped red region).…”
Section: Resultssupporting
confidence: 75%
“…The inability of near-bed turbulence to promote instability in the interface layer can also be explored on the basis of interaction between the turbulent vortical structures and the stably-stratified layer. In a TBL, the outer turbulence peak that increases in intensity with increasing Reynolds number is linked to the hairpin packets freely reaching into the log region of the near-bed layer 11,31,38 . On the other hand, it has been demonstrated that a layer of strong enough stratification behaves like a slip wall blocking the passage of vortices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 In this tunnel, a 1/2-inch tall nozzle blows air over a flat plate, hence its name wall jet, which results in a self-similar flow over the plate. [50][51][52] The boundary layer has two main flow regions, the near-wall flow exhibits the properties of a canonical zero pressure gradient turbulent boundary layer until a maximum velocity (u m ) is reached at wall height y m in the velocity profile. Above this point, a two-dimensional shear layer flow dominates, which is characterized by energetic, largescale structures.…”
Section: A the Rig And Measurement Proceduresmentioning
confidence: 99%